(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Objective Of This Study Is To Analyze Creative Problem-Solving Skill Components Of Undergraduate Students. The Data Were Collected With Questionnaires. The Samples, 20 Times Of Observation Variables, Were 332 Teachers Of Graduate Users Of 83 Schools In Bangkok By Using Simple Random Sampling. Statistics Used To Analyze Are Frequency, Percentage, Mean, Standard Deviation, And Confirmation Factor Analysis. The Findings Were Revealed That The Component Model Of Creative Problem-Solving Skill Of Undergraduate Students Was Harmoniousness With Empirical Data That Means The Developed Component Model Can Explain The Component Model Of Creative Problem-Solving Skill Of Undergraduate Students. Therefore, It Can Be Concluded That The Creative Problem-Solving Skill Components Of Undergraduate Students Consist Of 4 Aspects. The Aspect With The Highest Weight Is Flexibility (1.12) Followed By Fluency (0.95), Originality (0.89), And Elaboration (0.87) Respectively.